The prevalence of attention-deficit hyperactivity disorder and its related risk factors among children at elementary school in Shahroud - Azam Hamidzadeh; Mehrnaz Kharatha; Milad Bazghaleh; Hassan Basirinejad; Nasrin Fadae Aghdam; Hossein Ebrahimi (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Attention-deficit hyperactivity disorder (ADHD) is one of the most common reasons for visiting psychiatrists and psychologists. This study aimed to investigate the prevalence of ADHD and its related risk factors among children at elementary schools. MATERIALS AND METHODS: This cross-sectional study focused on teachers and parents of 779 elementary students who were selected through stratified cluster random sampling; Conners Parent and Teacher Questionnaires were used to collecting data. The data were analyzed by the use of descriptive statistics (frequency and percentage), independent samples t-test, Chi-square, one-way ANOVA, and linear regression. The significant level was set at 0.05. Results: According to teachers' responses, the prevalence of ADHD among students in elementary schools was 4.4%, whereas parents reported a prevalence of 0.5%. There was a significant relationship between childhood ADHD and marital status of parents, fathers' smoking habits, previous experience of living in rural areas, children's previous history of having diseases and using the medicine, previous history of ADHD, and psychological problems in the family. Conclusions: According to the study, teachers and parents suffer from a lack of knowledge about ADHD. Thus, the educational workshops and programs should be held for teachers, parents, and counselors to inform them about the procedures for timely diagnosis and treatment of ADHD.